2021
DOI: 10.4103/jfmpc.jfmpc_888_20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance (AMR) at the community level

Abstract: Context: The emergence of antimicrobial resistance (AMR) is a major public health crisis in India and globally. While national guidelines exist, the sources of data which form the basis of these guidelines are limited to a few well-established tertiary care centres. There is inadequate literature on AMR and antibiotic mismatch from India at community level and even less literature on AMR patterns from rural India. Aims: The aims of this study were as follows: 1) to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Therefore, our findings contradicted the main hypothesis with regard to human population. This finding is consistent with the research that was conducted to evaluate AMR at the community level in an urban and rural setting in Karnataka, India where it was revealed that AMR was high in community members in both rural and urban settings (Balachandra et al., 2021). In parallel with this study, two separate studies were conducted at the same study sites and results of these studies were already published as journal articles (Gunasekara et al., 2022; Gunasekera et al., 2022); a quantitative survey that was conducted to determine the knowledge, attitudes and perceptions (KAP) on antibiotics and AMR among the general public.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, our findings contradicted the main hypothesis with regard to human population. This finding is consistent with the research that was conducted to evaluate AMR at the community level in an urban and rural setting in Karnataka, India where it was revealed that AMR was high in community members in both rural and urban settings (Balachandra et al., 2021). In parallel with this study, two separate studies were conducted at the same study sites and results of these studies were already published as journal articles (Gunasekara et al., 2022; Gunasekera et al., 2022); a quantitative survey that was conducted to determine the knowledge, attitudes and perceptions (KAP) on antibiotics and AMR among the general public.…”
Section: Discussionsupporting
confidence: 91%
“…where it was revealed that AMR was high in community members in both rural and urban settings (Balachandra et al, 2021). In parallel with this study, two separate studies were conducted at the same study sites and results of these studies were already published as journal articles (Gunasekara et al, 2022;Gunasekera et al, 2022); a quantitative survey that was conducted to determine the knowledge, attitudes and perceptions (KAP) on antibiotics and AMR among the general public.…”
Section: Discussionmentioning
confidence: 89%
“…We found high rates of resistance of urinary pathogens to aminoglycosides, as has been described in previous studies. 16 …”
Section: Discussionmentioning
confidence: 99%
“…More than 25% of all K. pneumoniae and Pseudomonas spp isolates showed resistance to imipenem, and a similar proportion of all E. coli, Klebsiella spp and Pseudomonas spp isolates were resistant to fourth-generation cephalosporins. 16 …”
Section: Discussionmentioning
confidence: 99%
“…In 2019, 1.27 million deaths were directly attributable to AMR, with the highest burdens in sub-Saharan Africa and South Asia [3]. India, where this study is located, is among the highest AMR-prevalant countries [4], with 50% or more of E. coli, and 30% or more of Klebsiella in rural and urban settings, which are resistant to ciprofloxacin (a quinolone), and first-, second-and thirdgeneration cephalosporins [5][6][7], which are the first-line antibiotic treatments for bacterial diarrhoea and typhoid fever.…”
Section: Introductionmentioning
confidence: 99%